Luigi Nono: "Das atmende Klarsein": Text – Musik – Struktur - Reissig, Elfriede 1966- (Saarbrücken Pfau, 2014)
In Nono's oeuvre, "Das atmende Klarsein" is, as he himself said, a "breakthrough work". Originally conceived as part of the "tragedy of hearing" Prometeo, the piece underwent a process of emancipation during its genesis to become an independent, sonically highly complex work for small choir, bass flute and live electronics. Nono's enthusiastic exploration of new sound possibilities at the Freiburg Experimental Studio of the Heinrich Strobel Foundation became the impulse-giving work that would characterise his later work and ultimately lead Nono to the moving sound, the "suono mobile". Elfriede Elisabeth Reissig's study uses the sketch material to examine the genesis of Nono's work and to analyse his new sound aesthetic. (Translated with Deepl.com)
Keywords: Nono, Luigi -- 1924-1990; Musical analysis